Returning the Stolen Land (The Current Settlement of the Senamanenek Kampar Indigenous People with PT. Perkebunan Nusantara V) - Firdaus, Firdaus; Hendra, Rahmad; Samariadi, Samariadi; Firmanda, Hengki (Faculty of Law, Jambi University, 2023)
Conflicts over land between Senamanenek Indigenous Peoples of Kampar Regency and PT. Perkebunan Nusantara V has occurred since the early 1990. While national legislation acknowledges adat (customary) as a legitimate basis for rights, the current legal framework presents significant hurdles for communities seeking to assert their land claims based on adat rights. As an empirical legal research, this study tries to propose a new dispute resolution model to deal with the problem. This research found that government intervention as the owner of State-Owned Company capital determines the resolution of customary land disputes such as the PTPN V and Senamanenek Indigenous Peoples disputes. The settlement was carried out after receiving a presidential order and the United Indonesia Cabinet Limited Meeting results by returning the land and its contents from the PTPN V to the government. Then, the government hands over to individual Senamanenek Indigenous Peoples members who are issued certificates of ownership through the TORA mechanism.